Biodegradability of Trimethylbenzene Isomers under Denitrifying and Sulfate-Reducing Conditions - Fichtner, Thomas (Int J Environ Res Public Health, 2019)
Trimethylbenzene (TMB) isomers (1,2,3-TMB, 1,2,4-TMB, and 1,3,5-TMB) are often used as conservative tracers in anaerobic, contaminated aquifers for assessing BTEX (benzene, toluene, ethylbenzene, xylenes) biodegradation at field sites. However, uncertainties exist about the behavior of these compounds under anaerobic conditions. For this reason, the influence of various parameters (temperature, residence time) on the biodegradability of TMB isomers was investigated under denitrifying and sulfate-reducing conditions in microcosms and 1D-column experiments. Soil and groundwater contaminated with a cocktail of aromatic hydrocarbons including the TMB isomers, both collected from an industrial site in Berlin, Germany, were used for the laboratory investigations. A continuous and complete biodegradation of 1,3,5-TMB and 1,2,4-TMB under denitrifying conditions was observed independent of realized temperature (10–20 °C) and residence time. Biodegradation of 1,2,3-TMB started after longer lag-phases and was not continuous over the whole experimental period; a strong dependence on temperature and residence time was identified. The biodegradability of all TMB isomers under sulfate-reducing conditions was continuous and complete at higher temperatures (20 °C), whereas no degradation was observed for lower temperatures (10 °C). First-order biodegradation rate constants ranged from 0.05 to 0.21 d(−1) for 1,3,5-TMB and 1,2,4-TMB and from 0.01 to 0.11 d(−1) for 1,2,3-TMB.